Mahovna flora fitogeografskega podobmočja Dravski Kozjak (Slovenija) - Martinčič, Andrej (Hladnikia (Ljubljana), 2010)
The study gives results on new bryophyte records of phytogeographical subregion Kozjak (part of Alpine phytogeographical region) as well as the previous reports from literature and data from LJU. In total, 306 species are reported from the investigated subregion, 62 liverworts and 244 mosses. Among them 193 species are reported for the first time for phytogeographical subregion Kozjak. In the national Red List are included 24 species and 2 species in the Red Data Book of European Bryophytes (ECCB 1995): Anacamptodon splachoides in the endangered (E) category and Brachythecium geheebii in the rare (R) category.
Keywords: Dravski Kozjak; fitogeografija; flora; mahovi; Slovenia; Slovenija